Prevalence of Diabetes and Prediabetes according to Fasting Plasma Glucose and HbA1c - Ja Young Jeon; Seung-Hyun Ko; Hyuk-Sang Kwon; Nan Hee Kim; Jae Hyeon Kim; Chul Sik Kim; Kee-Ho Song; Jong Chul Won; Soo Lim; Sung Hee Choi; Myoung-jin Jang; Yuna Kim; et al. (Diabetes & Metabolism Journal, 2013)
BackgroundDue to the inconvenience of performing oral glucose tolerance tests and day to day variability in glucose level, glycated hemoglobin (HbA1c) has been recommended by the American Diabetes Association as a method to diagnose diabetes. In addition, the Korean Diabetes Association has also recommended the use of HbA1c as a diagnostic test for diabetes. In this study, we evaluated the prevalence of diabetes according to fasting plasma glucose (FPG) level only or the combination of FPG and HbA1c tests.MethodsData from the 2011 Korea National Health and Nutrition Examination Survey (KNHANES) were analyzed. Among 5,811 subjects aged 30 years or older, 5,020 were selected after excluding the data of fasting time <8 hours, missing values from fasting glucose or HbA1c level, previous diagnosis of diabetes made by physicians, or current use of antidiabetic medications. Diabetes was defined as FPG ≥126 mg/dL, previous diagnosis of diabetes made by a medical doctor, current use of antidiabetic medications, and/or HbA1c ≥6.5%. Prediabetes was defined as FPG of 100 to 125 mg/dL and/or HbA1c of 5.7% to 6.4%.ResultsWhen we used FPG only, the prevalence of diabetes and prediabetes were 10.5% (men, 12.6%; women, 8.5%) and 19.3% (men, 23.8%; women, 14.9%), respectively. When HbA1c was included as a diagnostic test, the prevalence of diabetes and prediabetes increased to 12.4% (men, 14.5%; women, 10.4%) and 38.3% (men, 41%; women, 35.7%), respectively. Participants with HbA1c ≥6.5% and fasting glucose level <126 mg/dL were older and had lower estimated glomerular filtration rate.ConclusionWe concluded that using fasting glucose level only may result in an underestimation of diabetes and prediabetes. HbA1c is an acceptable complementary diagnostic test for diabetes in Korean patients. However, national standardization is needed to order to use HbA1c as a diagnostic method of diabetes and prediabetes.